Job crafting as a tool to increase motivation and employee engagement - N. Yu. Kaufman; S. Yu. Zelentsova (Вестник университета)
The subject of the research in the article is the tools of motivation and involvement of personnel in the organization. The study examines the theoretical aspects of motivation and involvement of personnel, determines the relevance of self-development of the employees’ potential of modern organizations. The development perspective of personnel basic skills in the 21st century is shown, which includes, in addition to the traditionally necessary professional hard skills and soft skills, also existential skills containing the ability to self-development and self-learning. The concept of job crafting as a tool for staff self-development is proposed, the main idea of which is that in order for an employee to be involved in the workflow, it is necessary to reconsider the attitude to work according to the following criteria: the approach to completing tasks, the nature of interactions with colleagues, thinking when doing work. A comparative analysis of job crafting and the concept of kaizen (which is used when an organization needs changes to increase competitiveness) is carried out. Job crafting is relevant as a motivational tool when employees initiate changes themselves and form their own working environment in such a way that it meets their individual needs by adjusting the prevailing requirements of work and resources.